Creation of software to help cardiac surgeons - Th. . Sénage; R. . Gaudin; M. . Michel; A. . Mugniot; Ch. . Périgaud; S. . Pattier; O. . Al Habash; D. . Duveau; O. . Baron; Ph. . Despins; J. Ch. Roussel (Вестник хирургии имени И.И. Грекова)
Abstract Background: The writing of surgical and hospitalization reports is time-consuming and does not necessarily enable the increment of a statistical database, tool that is indispensable nowadays to evaluate unit activity or to carry out scientific studies. In order to prevent this double data capture, a computer tool, named CordaBase, has been developed by surgeons and set up in a cardiac surgery unit. Materials and Methods: CordaBase is an interactive software that stores medical data. Thanks to its intuitive interface, CordaBase stores data which is classified chronologically in the following categories: past medical history, preoperative assessment, operating gesture, stay in intensive care unit, stay in wards and evolution/monitoring after discharge. This date, stored in an Access base, are then used in the creation of personalized surgical and hospitalization reports. All the data is permanently available and can be used for the carrying out of scientific works or for the evaluation of the unit activity. Results: From March 2009 to December 2010, 2617 consecutive patients operated on in a Cardiac Surgery Unit were recorded prospectively in the software. All of this stored data assisted the surgeon in his or her administrative tasks, thanks to personalized surgical and hospitalization reports, immediately at the secretariat’s disposal. The database, which is requisitely filled by administrative work, enables the carrying out of any statistical study on all unit activity. Conclusion: With a hindsight of almost 2 years, CordaBase has proven its usefulness in an active cardiac surgery unit, both on an administrative and scientific level. The computerized reports have lightened the medical secretariat’s workload and statistical studies have now become possible without having to take the paper medical files out again. In the years to come, the accumulation of medical data prospectively or retrospectively stored will surely confirm the potential of the use of such a software.